Uganda: Systematic analysis of world market and domestic production shocks - Mukashov, Askar; Jones, Eleanor; Thurlow, James (International Food Policy Research Institute, 2025)
Achieving development goals is subject to economic uncertainties, yet policymaking rarely accounts for these risks. This Country Brief quantifies the risks facing Uganda’s economy and population, focusing on two primary sources: 1) External risks stemming from shocks in international commodity prices and foreign capital flows and 2) Domestic risks associated with production shocks in volatile sectors of the Uganda economy, such as primary agriculture and hydropower electricity generation, are often caused by extreme weather. The significance of these risks is assessed based on the range of the shocks’ impacts on four main economic and development indicators: total GDP, private consumption, poverty rate, and prevalence of undernourishment. The analysis uses data mining methods to simultaneously sample many shocks from historical data, con structing a comprehensive set of realistic shock scenarios for Uganda. A country-specific, economywide Computable General Equilibrium (CGE) model then simulates the impacts of these shocks on both total and sector-specific economic outcomes, deriving changes in poverty and undernourishment for each shock scenario. Finally, machine learning techniques are applied to obtain metrics for the relative im portance of different risk factors. The results suggest that domestic production volatility is the primary risk factor affecting GDP and poverty in Uganda, whereas world markets and domestic risks are equally important for household consumption and undernourishment. Individually, the most critical risk factors identified include production volatility in root crops, volatility in foreign capital flows, and volatility in fishery production, with the latter being particularly significant for rural low-income households. Understanding these economic risks is a critical first step in facilitating discussions on potential risk management strategies, such as promoting domestic productivity growth and diversifying economic activity away from high-risk sectors.